Accessibility Level of Disabled Parking Areas at Modern Shopping Centers in Special Region of Yogyakarta - Pujiyanti, Indah; Rahman, Norainah Abdul (Universitas Aisyiyah Yogyakarta, 2024)
discrimination, including people with disabilities. In regulations in Indonesia has also regulated if every public building must provide an accesibility factor in its planning. This convenience is in the form of ease in accessing and using all public facilities. A special disabled parking area is one of the requirements in the application of aspects of building convenience. The availability of special parking areas for people with disabilities in public facilities is one of the starting points in identifying how accessible a building is. In this study, we will discuss the analysis of the level of accessibility of the application of special disabled parking areas in modern shopping centers in the Special Region of Yogyakarta. Modern shopping centers are public facilities that are often accessed by people with various age differences and conditions. Special Region of Yogyakarta also has one of the missions to become an inclusive province. Therefore, this study aims to determine the availability and level of accessibility of standard disabled parking areas in modern shopping centers in the Special Region of Yogyakarta. The method used is a quantitative method with direct observation through measurements and observations which are then compared with the standard for disabled parking areas according to Indonesian regulations. The results of this study are known that 80% of shopping centers in Yogyakarta have disabled parking areas with a high level of accessibility, namely by implementing 4 elements that comply with standards and the dominant problem that exists for the implementation of disabled parking in Yogyakarta shopping centers is the presence of barriers in front of the parking area so that the parking area cannot be used optimally.